Transformations in the reaction products and properties of carbonation-cured CSA cements exposed to a sulfate attack - Joonho Seo; Daeik Jang; Jin-Ho Bae; Naru Kim; Jihoon Park; Alam Cho; H.K. Lee (Journal of CO2 Utilization)
Reaction products and properties of carbonation-cured calcium sulfoaluminate (CSA) cements exposed to a sulfate attack were explored in an attempt to elucidate their durability aspects and potential opportunities for practical applications. CSA paste samples were either normally cured or carbonation-cured and subsequently immersed in a Na2SO4 solution. The test results indicated that carbonation curing hindered the delayed ettringite formation induced by a sulfate attack, especially in the carbonation-cured samples with an m-value of 0.5 or 1.0. In addition, these carbonation-cured samples exhibited less degrees of weight and mass loss compared to the normally cured samples. Given these test results, the carbonation-cured samples with an m-value of 0.5 – 1.0 were found to be the most durable against the Na2SO4 attack. The outcomes of this study can be viewed important as they provide a fundamental data source for developing guidelines on producing highly durable materials by combining mixture proportioning and carbonation curing when CSA cements are applied in areas particularly susceptible to sulfate attacks.